Stem cell treatment for type 1 diabetes - Li, Ming; Ikehara, Susumu (Frontiers in Cell and Developmental Biology, 2014)
Type 1 diabetes mellitus (T1DM) is a common chronic disease in children, characterized by a loss of  cells, which results in defects in insulin secretion and hyperglycemia. Chronic hyperglycemia causes diabetic complications, including diabetic nephropathy, neuropathy and retinopathy. Curative therapies mainly include diet and insulin administration. Although hyperglycemia can be improved by insulin administration, exogenous insulin injection cannot successfully mimic the insulin secretion from normal  cells, which keeps blood glucose levels within the normal range all the time. Islet and pancreas transplantation achieves better glucose control, but there is a lack of organ donors. Cell based therapies have also been attempted to treat T1DM. Stem cells such as embryonic stem cells, induced pluripotent stem cells and tissue stem cells (TSCs) such as bone marrow-, adipose tissue- and cord blood-derived stem cells, have been shown to generate insulin-producing cells. In this review, we summarize the most-recently available information about T1DM and the use of TSCs to treat T1DM.